2017
DOI: 10.1111/geer.12111
|View full text |Cite
|
Sign up to set email alerts
|

Bounded Rationality in Principal-Agent Relationships

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…These principal-agent problems were noted between NHIA and health service providers in the area of prescribing and dispensing of drugs and medicines to clients. The private health services providers were more 'self-seeking' or 'selfish' with more moral hazards than their public counterparts, which agrees with a number of studies on agents' self-interests/selfseeking (Worsham & Gatrell, 2005;Winter, et al 2008;Erlei & Schenk-Mathes, 2016). Other problems identified in this study is that the reward system for performance is not clear, this created some mistrust or suspicion between the principal (NHIA) and the agent (service providers).…”
Section: Discussion Of Findings Principal-agent Issues and Problems In The Implementation Of Nhissupporting
confidence: 85%
See 1 more Smart Citation
“…These principal-agent problems were noted between NHIA and health service providers in the area of prescribing and dispensing of drugs and medicines to clients. The private health services providers were more 'self-seeking' or 'selfish' with more moral hazards than their public counterparts, which agrees with a number of studies on agents' self-interests/selfseeking (Worsham & Gatrell, 2005;Winter, et al 2008;Erlei & Schenk-Mathes, 2016). Other problems identified in this study is that the reward system for performance is not clear, this created some mistrust or suspicion between the principal (NHIA) and the agent (service providers).…”
Section: Discussion Of Findings Principal-agent Issues and Problems In The Implementation Of Nhissupporting
confidence: 85%
“…Similarly, Moe (1984) agents want to maximise their own interests against their principals. Thus, in the principal-agent relationship, there is issue of self-interest/self-seeking of one actor against the interest of another-'moral hazards' (Bossert, 1998;Worsham & Gatrell, 2005;Winter, et al, 2008;Erlei & Schenk-Mathes, 2016). Another issue or problem in principal-agent relationship is the procedure use in rewarding the agent (benefits/rewards).…”
Section: Theoretical Perspective: Principal-agency Theorymentioning
confidence: 99%
“…Bounded rationalities of the defender are mainly expressed as supervision will, which is determined through the strategy selection of the government with setting ρ as selection probability of β1 and 1−ρ as selection probability of β 2 . Bounded rationalities of the collusive parties are also mainly expressed as their own moral constraints and interpretation of the supervision [26]. For the collusive parties, apart from economic interests of rent seeking, their moral constraint and interpretation of the supervision will also influence collusive behavior.…”
Section: The General Settingmentioning
confidence: 99%
“…This is a significant gap in the literature, as it is unrealistic to assume that stylized, rational Principals can fully characterize real-world, human Principals. Indeed, laboratory PA experiments with human participants have shown that bounded rationality is needed to explaining marked deviations between equilibria reached by human participants and theoretical predictions (Erlei & Schenk-Mathes, 2017).…”
Section: Introductionmentioning
confidence: 99%